Effect of nutrition-genotype interaction on protein and casein synthesis in goat milk of the Malagueña breed - De la Torre G.; Serradilla J.M.; Ares J.L.; Rodríguez Osorio M.; Sanz Sampelayo M.R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
An experiment was carried out using twelve goats of the Malagueña breed. Six of these animals belonged to the high capability (three BB and three AB) and six to the low capability (three FF and three EF) genotype for as1-casein synthesis. They were fed two different diets according particularly to their crude protein content: 13.6% (D1) and 17.7% (D2). Within each genotype, the animals were allocated to a 2x2 Latin square design with three repetitions. Together with the metabolizable energy intakes (kJ/kg0.75.d), the milk protein (g/kg0.75.d) and casein (g/kg0.75.d) synthesis were determined. From the corresponding results it was first inferred that the milk protein and casein synthesis depended on the metabolizable energy intake, these quantities being higher for the high capability genotype for as1-casein animals and for the higher protein content in the diet. The effects of genotype and protein content in the diet were mainly independent. So, one way of exploiting the genetic potential expression for milk protein and casein synthesis, could be to make use of diets with a high content of crude protein.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)